The mistakes and the misconceptions of the eight grade students on the subject of angles - Tuna, Abdulkadir; Biber, Çağrı; Korkmaz, Samet (Bastas Publications, 2013)
The purpose of this study was to determine the learning levels, mistakes, and misconceptions of the 8th grade students on the subject of “angles in geometry” as well as the possible reasons for these situations. Research sample consisted of 30 students attending the 8th grade of a middle school located in the central district of a northern province of Turkey during the 2012 – 2013 academic year. 4 open-ended questions were used in this study. Firstly, the answers given were divided into two: correct and incorrect. Then, incorrect answers were split into sub-categories and tabulated. According to the results of the study, (1) students paid attention to the physical appearances of geometric figures alone without taking into consideration their geometric properties; (2) although they detected some geometric properties of figures, they failed to associate these properties with other knowledge required for solution; (3) they generalized a property that was valid for only a specific condition over different situations; (4) and they did not fully comprehend the concept of parallelism on the subject of angles.
Keywords: 4. Education